“Student success is not an individual achievement” – Motivation and teacher education in the digital age - Chrappán, Magdolna; Buda, András (Central European Journal of Educational Research, 2026)
The motivation of student teachers is a key issue in contemporary teacher education, typically examined through psychological theories focusing on individual learning processes. This paper does not aim to provide a comprehensive literature review; instead, it offers a conceptual reflection that pays tribute to the work of Gabriella Pusztai, whose research highlights the social embeddedness of student achievement, integration, and persistence. Building on her approach, the study integrates psychological, pedagogical, and sociological perspectives to reinterpret motivation in pedagogical courses. It proposes a three-dimensional framework consisting of integration, relevance, and identity, emphasising that motivation is a context-dependent and dynamically changing phenomenon. The paper also examines how digital learning environments reshape motivational conditions by influencing autonomy, relatedness, engagement, and perceived relevance. The findings suggest that understanding student motivation requires moving beyond individual-level explanations and recognising the decisive role of relational, institutional, and technological contexts.